Identification of Putative RuBisCo Activase (TaRca1)—The Catalytic Chaperone Regulating Carbon Assimilatory Pathway in Wheat (Triticum aestivum) under the Heat Stress - Kumar, Ranjeet R.; Goswami, Suneha; Singh, Khushboo; Dubey, Kavita; Singh, Shweta; Sharma, Renu; Verma, Neeraj; Kala, Yugal K.; Rai, Gyanendra K.; Grover, Monendra; Mishra, Dwijesh C.; Singh, Bhupinder; et al. (Frontiers in Plant Science, 2016)
RuBisCo activase (Rca) is a catalytic chaperone involved in modulating the activity of RuBisCo (key enzyme of photosynthetic pathway). Here, we identified eight novel transcripts from wheat through data mining predicted to be Rca and cloned a transcript of 1.4 kb from cv. HD2985, named as TaRca1 (GenBank acc. no. KC776912). Single copy number of TaRca1 was observed in wheat genome. Expression analysis in diverse wheat genotypes (HD2985, Halna, PBW621 and HD2329) showed very high relative expression of TaRca1 in Halna under control and HS-treated, as compared to other cultivars at different stages of growth. TaRca1 protein was predicted to be chloroplast-localized with numerous potential phosphorylation sites. Nothern blot analysis showed maximum accumulation of TaRca1 transcript in thermotolerant cv. during mealy-ripe stage, as compared to thermosusceptible. Decrease in the photosynthetic parameters was observed in all the cultivars, except PBW621 in response to HS. We observed significant increase in the Rca activity in all the cultivars under HS at different stages of growth. HS causes decrease in the RuBisCo activity; maximum reduction was observed during pollination stage in thermosusceptible cvs. as validated through immunoblotting. We observed uniform carbon distribution in different tissues of thermotolerant cvs., as compared to thermosusceptible. Similarly, tolerance level of leaf was observed maximum in Halna having high Rca activity under HS. A positive correlation was observed between the transcript and activity of TaRca1 in HS-treated Halna. Similarly, TaRca1 enzyme showed positive correlation with the activity of RuBisCo. There is, however, need to manipulate the thermal stability of TaRca1 enzyme through protein engineering for sustaining the photosynthetic rate under HS – a novel approach towards development of ‘climate-smart’ crop.